mHealth4Afrika - Co-designing an Integrated Solution for Resource Constrained Environments - Cunningham, Miriam; Cunningham, Paul; van Greunen, Darelle (Journal of Health Informatics in Africa, 2018)
Background: mHealth4Afrika is a collaborative research and innovation project, co-funded under Horizon 2020. It is focused on supporting Sustainable Development Goal 3 and Horizon 2020 Societal challenges by researching and evaluating the potential impact of co-designing and developing an open source, multilingual enabled mHealth platform to support quality community-based primary maternal healthcare delivery at semi-urban, rural and deep rural clinics, based on end-user requirements in Southern Africa (Malawi, South Africa), East Africa (Kenya) & Horn of Africa (Ethiopia). Methods: A mixed methods strategy is applied. For technical development of the platform, design science research techniques are applied. The various platform iterations are implemented using an agile development process. Qualitative data collection and ethnographic observation was used during the needs requirements and base line study and validation of system iterations. These methods support regular interaction with policy makers, district and clinic managers and healthcare workers as part of the co-design process. Results: This paper aims to share insights into the co-design process to develop a platform that integrates Electronic Medical Records, Electronic Health Records, medical sensors and visualisation tools, and automatically generates monthly program indicators. Conclusions: mHealth4Afrika has developed a custom application to strengthen primary healthcare delivery in resource-constrained environments. It supports a range of interdependent programs defined in consultation with key stakeholders. This is achieved by interacting with a data model set up in DHIS2 via a WebAPI to facilitate holistic monitoring of a patient’s well being.